The Influence of Balinese Cocktail and Liquor-Based Beverage International Innovation on Guest Buying Interest at 69 Bar & Resto Kuta Bali - Widnyana, Gede Rico Hardiana; Wisnawa, I Made Bayu; Anggreni, Ni Putu Yunik (LPPM Universitas Dhyana Pura, 2026)
The intense competition in the food and beverage industry in Kuta, Bali, requires continuous product innovation to sustain consumer purchase intention. This study aims to analyze the effect of International Cocktail Innovation (X₁) and Balinese Arak-Based Beverages (X₂) on Guest Purchase Intention (Y) at 69 Bar & Resto Kuta Bali. A quantitative associative approach was employed, involving 80 respondents selected through purposive sampling from a population of 87,087 guests over the period of January 2025–January 2026. Data were collected using a Likert-scale questionnaire and analyzed with multiple linear regression via SPSS 26. The results revealed that both international cocktail innovation (t = 3.944, p < 0.05) and Balinese arak-based beverages (t = 3.396, p < 0.05) have a positive and significant partial effect on purchase intention. Simultaneously, the two variables significantly influence purchase intention (F = 48.997, p < 0.05). The coefficient of determination (R²) of 0.560 indicates that 56% of purchase intention variance is explained by these two variables, with international cocktail innovation being the dominant factor. These findings suggest that combining modern mixology techniques with local wisdom in the form of Balinese arak can effectively enhance consumer appeal and experience. The study recommends strengthening bartender storytelling skills and promoting experience-based marketing to further increase competitiveness.